[Exposition Universelle de Bruxelles 1958]. (Amsterdam : Stichting Prometheus, 1958)
Bibliotheek Camille Huysmans
Themanummer van: 'Revue Internationale d'Eclairage', 1958, nr 3-4
Frans
Monografie
Keywords: wereldtentoonstelling 1958